A Case Study On YTL International Power Berhad - Haji Abd Mubin, Mohamad Razif (2003)
In Malaysia, YTL is the first power generation company contributing to the efficiency of the electricity generation of the country. YTL is facing stiff competition from its rivals of getting bigger market share of the growing industry.